A comparative study of the effect of spray drying and hot-melt extrusion on the properties of amorphous solid dispersions containing felodipine. (10th July 2013) - Mahmah, Osama; Tabbakh, Rami; Kelly, Adrian; Paradkar, Anant
Abstract: Objectives: To compare the properties of solid dispersions of felodipine for oral bioavailability enhancement using two different polymers, polyvinylpyrrolidone (PVP) and hydroxypropyl methylcellulose acetate succinate (HPMCAS), by hot-melt extrusion (HME) and spray drying. Methods: Felodipine solid dispersions were prepared by HME and spray drying techniques. PVP and HPMCAS were used as polymer matrices at different drug : polymer ratios (1 : 1, 1 : 2 and 1 : 3). Detailed characterization was performed using differential scanning calorimetry, powder X-ray diffractometry, scanning electron microscopy and in-vitro dissolution testing. Dissolution profiles were evaluated in the presence of sodium dodecyl sulphate. Stability of different solid dispersions was studied under accelerated conditions (40°C/75% RH) over 8 weeks. Key findings: Spray-dried formulations were found to release felodipine faster than melt extruded formulations for both polymer matrices. Solid dispersions containing HMPCAS exhibited higher drug release rates and better wettability than those produced with a PVP matrix. No significant differences in stability were observed except with HPMCAS at a 1 : 1 ratio, where crystallization was detected in spray-dried formulations. Conclusions: Solid dispersions of felodipine produced by spray drying exhibited more rapid drug release than corresponding melt extruded formulations, although in some cases improved stability was observed for melt extruded formulations.